Transcripts as modifiers of phenotypic variability in hereditary transthyretin-mediated amyloidosis biopsies - Gouveia, Ana Maria Furtado (2022)
Herditary transthyretin-mediated amyloidosis (ATTRv) is a severe disease, dominat, autosomal amyloidois characterized by a progressive polyneuropathy, due to a point mutation in TTR gene, causing the deposition of amyloid fibrils in peripheric nerves. Due to wide variability in age-at-onset (AO), two main groups were stablished, early-onset (AO˂50 years) and late-onset (AO≥50 years). The main goal of this project was the analysis of RNA transcripts theta could act as modifiers of phenotypic variablility in ATTRv patient biopsies. Therefore, it was stablished wo main steps: (A) extraction and quantification of RNA from paraffin biopsies and (B) analysis of RNA transcripts that will allow to explain phenotypic variability in ATTRv. Five differentially expressed genes were identified in salivar gland samples. MGAM2 gene stood out between the other four genes due to its higher expression in the early AO group. This gene may be associated with the inhibition of a protectice factor that was not identified yet. Overall, our study may be a precursor to future exploration of proein-protein interactions, as well as the SNPs detection in differentially expressed genes that may modulate the phenotypic variability in ATTRv.